ANALISIS STILISTIKA DAN NILAI PENDIDIKAN TEMBANG PUPUH SINOM PADA SERAT WULANG DALEM WARNI -WARNI KARYA PAKU BUWONO IX SERTA RELEVANSINYA T ERHADAP PEMBELAJARAN TEMBANG MACAPAT PUPUH SINOM PADA SISWA SMP - Susanti Susanti; Yant Mujiyanto; Budi Waluyo (Universitas Sebelas Maret, 2018)
This research was research qualify research to do some stylistic analysis and education values which inside in the pupuh Sinom text on Wulang Dalem Warni-Warni made by Paku Buwono IX. Although this research for relevance knowledge or not if text pupuh Sinom in the Wulang Dalem Warni-Warni make for material of study in the junior high school grade VIII. Data base for used some of the document analysis and interviews in the data test validity and use triangulation metod and data base analysis with interactive technical which have three component: (1) data reduction, (2) data display, and (3) conclution drawing. This result data which is stylistic analysis, education values and relevance text pupuh Sinom in the Wulang Dalem Warni-Warni which is use for basic teaching in junior high school. Stilistic analysis on the text pupuh Sinom which have sound style, word style, sentence style, figure of speech, imagery, and also education values have inside in the education of religious, morality education, social education, and culture education. Pupuh Sinom text in the Wulang Dalem Warni-Warni have relevance if make for material of study in the junior high school level grade VIII semester II connected basic competition reading tembang Sinom.